Expression of myostatin in human hematopoietic cells unveils novel autocrine/paracrine actions for the hormone. Issue 5 (28th October 2018) - Fernández‐Nocelo, Susana; Gallego, Rosalía; Costoya, José A.; Arce, Víctor M.
Abstract: Myostatin is a member of the transforming growth factor β (TGFβ) superfamily that has a well‐established role as a mediator of muscle growth and development. However, myostatin is now emerging as a pleiotropic hormone with multiple actions in the regulation of the metabolism as well as several aspects of both cardiac and smooth muscle cells physiology. In addition, myostatin is also expressed in several nonmuscular cells where its physiological role remains to be elucidated in most cases. In this report, we have shown that both myostatin and its receptor system are expressed in blood cells and in hematopoietic cell lines. Furthermore, myostatin treatment promotes differentiation of both HL60 and K562 cells through a mechanism that involves activation of extracellular signal‐regulated kinases 1/2 and p38‐mitogen‐activated protein kinase, thus leading to the possibility that myostatin may be a paracrine/autocrine factor involved in the control of haematopoiesis. In addition, the presence of myostatin expression in immune cells could envisage a novel role for the hormone in the pathogenesis of inflammatory diseases. Abstract : Myostatin produced by haematopoietic progenitors could act as an autocrine/paracrine factor regulating haematopoiesis. In addition, myostatin production by peripheral blood cells could be involved in the pathogenesis of both inflammatory myopathies and other inflammatory diseases.